COMPARISON OF EFFICACY OF PERMETHRIN 5% CREAM WITH CROTAMITON 10% CREAM IN PATIENTS WITH SCABIES - Rao, Muhammad Ali; Raza, Naeem; Faheem, Muhammad; Saleem, Muhammad Amer (Journal of Ayub Medical College Abbottabad, 2019)
Background: Scabies is a common dermatological presentation in Pakistan. Permethrin and Crotamiton both are used widely for treating scabies. As there is no local study available regarding comparison of efficacy of Permethrin and Crotamiton in patients of scabies, current study was undertaken. The objective of the study was to compare the efficacy of 5% Permethrin with 10% Crotamiton in patients of scabies. Methods: A Randomized control trial was conducted at Dermatology Department, Military Hospital, Rawalpindi. One hundred and sixty patients with scabies (diagnosis made by scraping the burrows to extract mite, larva or eggs and to see under light microscope) were randomly assigned either to Permethrin or Crotamiton group. Patients were followed over for 4 weeks to determine the effectiveness of either treatment. Results: A total of 160 patients were included in the study with a mean age of 45.49±17.047 years and ranging from 13-65 years. One hundred and one patients (63.1%) were male and remaining 59 patients (26.9%) were female. Treatment was effective in 81.3% patients being treated with 5% Permethrin and 53.8% in 10% Crotamiton group. Comparison of treatment showed superiority of 5% Permethrin over 10% Crotamiton (p=0.001). There was no effect of age and gender on this outcome difference. Conclusion: Our study concludes that 5% Permethrin cream is significantly superior to 10% Crotamiton cream in treating patients of scabies (81.3% vs. 53.8%, p=0.001). Keywords: Sacroptes Scabei; Permetherin; Crotamiton; Scabies